Population screening for congenital hypothyroidism. Issue 6215 (8th March 1980) - Hulse, J A; Grant, D B; Clayton, B E; Lilly, P; Jackson, D; Spracklan, A; Edwards, R W; Nurse, D
Abstract : A pilot screening programme for congenital hypothyroidism covering most of North London, Essex, Bedfordshire, and Hertfordshire entailed carrying out an assay of thyroid-stimulating hormone on single Guthrie dried blood spots. During one year 87 444 babies were screened and 26 cases of primary congenital hypothyroidism detected, giving an incidence of 1:3363. Only two cases (7.7%) had already been diagnosed on clinical grounds before the results of screening became available. In two other babies the diagnosis was delayed. The programme thus resulted in the early treatment of 22 babies, eight of whom already had pronounced features of hypothyroidism that had not been detected on routine clinical examinations. Although definitive evidence will not be available for some years, the results suggest that the prognosis for most of these babies is likely to be improved by early diagnosis; thus the introduction of national screening should be delayed no longer.